Hubungan Mekanisme Koping dengan Tingkat Stres Pada Pasien Fraktur - Rosalina Primarta Mesuri; Emil Huriani; Gusti Sumarsih (NERS Jurnal Keperawatan, 2014)
Fracture can lead to losing of physical function that could become stressor which create stress. Patients experience stress was looked nervous, loosed appetite, worried and they tried to avoid their self with be quiet and day dreaming. The purpose of this study was to determine the relationship between coping mechanism and stress level of fracture patient at the Trauma center DR M. Djamil hospital Padang year 2013. This was a correlational study using cross sectional approach. Total sample of this were 60 respondents that taken by purposive sampling. Data collection using stress level questionnaire and COPE questionnaire. The univariate analysis was using frequency distribution and the bivariate analysis was using Lambda. The result showed that 50% respondents low experiencing level of stress, 68,3% using adaptive coping mechanism. The was a significant relationship between coping mechanism and the stress level with weak influence and positive direction (p=0,004) and (r=0,300). It is suggest to the nurses to pay attention for signs and symptoms stress on patient and to fracture patients with maladaptive coping mechanism to ask someone for solve the stress, to give positive appraisal and suggestion to using adaptive coping mechanism.